Beyond amyloid: Getting real about nonamyloid targets in Alzheimer's disease. Issue 4 (1st July 2013) - Herrup, Karl; Carrillo, Maria C.; Schenk, Dale; Cacace, Angela; DeSanti, Susan; Fremeau, Robert; Bhat, Ratan; Glicksman, Marcie; May, Patrick; Swerdlow, Russell; Van Eldik, Linda J.; Bain, Lisa J.; et al.
Abstract: For decades, researchers have focused primarily on a pathway initiated by amyloid beta aggregation, amyloid deposition, and accumulation in the brain as the key mechanism underlying the disease and the most important treatment target. However, evidence increasingly suggests that amyloid is deposited early during the course of disease, even prior to the onset of clinical symptoms. Thus, targeting amyloid in patients with mild to moderate Alzheimer's disease (AD), as past failed clinical trials have done, may be insufficient to halt further disease progression. Scientists are investigating other molecular and cellular pathways and processes that contribute to AD pathogenesis. Thus, the Alzheimer's Association's Research Roundtable convened a meeting in April 2012 to move beyond amyloid and explore AD as a complex multifactorial disease, with the goal of using a more inclusive perspective to identify novel treatment strategies.